CALCULATION OF HOMA AND BIRD AROMATICITY INDICES, NLO AND NBO PROPERTIES OF BENIDIPINE - Kandemirli, Fatma; Tuncel, Derya Hilal; Genç, Fatma (Istanbul Ticaret Universitesi, 2024)
Benidipine hydrochloride, being the derivate of 1,4-dihydropyridine is a calcium channel blocker antihypertensive drug. The aromaticity, natural bond orbital (NBO) and Nonlinear Optical (NLO) parameters properties of Benidipine (BEN) and BENHCl compounds were theoretically investigated using density functional theory (DFT) electronic structure method. Among the values of common aromaticity indices, the Harmonic Oscillator Aromaticity Model (HOMA) and BIRD's (Aromaticity Index) for electronic delocalization show that the aromaticity of the nitrophenyl group is higher in BEN and BENHCl compounds, and also the aromaticity in the gas phase is higher than that in water, octanol and DMF phase. In compound BEN, it was observed that as the dielectric constant of the medium increased, the aromaticity difference increased slightly. In the compound BEN, the correlation coefficient between HOMA values and aromatic fluctuation index (FLU), para delocalization index (PDI) and para-linear response (PLR) for the nitrophenyl group is higher than that the phenyl group. Donor-acceptor transitions, stabilization energies, intramolecular charge transfer were determined by natural population analyses. NLO parameters such as dipole moment, polarisibility and first order hyperpolarizability values of the BEN and BENHCl compound were also studied.